Comparison of maternal and fetal outcomes in mothers with non-congenital mitral valve stenosis and healthy control - Sima sobhani Shari; Tooba Kazemi; Ali Bidokhti; Seyed Mohammad Riahi (Elsevier, 2024)
Background: Physiological changes during pregnancy cause complications in mothers with mitral stenosis and their infants. This study was designed to assess maternal and fetal pregnancy outcomes in women with rheumatic mitral valve stenosis and compare them with the control group. Materials and methods: This study is a case-control study on 153 pregnant women, including 51 with mitral stenosis (MS) and 102 without MS as the control group, between 2007-2022. For each studied patient, two control participants were selected and matched in residence, age, and year of pregnancy. SPSS version 22 was used for data analysis. Results: The mean age was 31.7 ± 4.6 years in cases and 31.6 ± 4.7 in the healthy controls. Demographic variables were not significantly different between the case and control groups. The rate of stillbirth (5.9% vs. 0.0%), %), NICU admission (13.7% vs. 2.0%), and IUGR (5.9% vs. 0.0%) were higher in the fetal case group compared with the control group. On the other hand, maternal outcomes, including pulmonary edema (13.7% vs. 0.0%), ICU admission (23.5% vs. 0.0%), limb edema (15.7% vs. 0.0%), dyspnea (37.3% vs. 0.0%), pulmonary hypertension (9.8% vs. 0.0%), palpitations (21.1% vs. 0.0%) and hospital admission during pregnancy (37.2% vs. 4.9%) were statistically more common in the case groups. Conclusions: Pregnancy is associated with significant fetomaternal morbidities in women with mitral valve heart disease. So they need a multidisciplinary approach in preconception and antenatal care.